(untitled) - Stair, Lila B. (New York, NY., 2006)
It takes a lot of time and effort to prepare for a profession—and this book takes you every step of the way to reaching that goal. Ideal whether you are college-bound or are ready to go back to school to gain the necessary degree, Careers in Business explores specific professions and then helps you determine which job in that profession bests suits you.
Keywords: Business; Vocational guidance; United States